2006
DOI: 10.1016/j.livprodsci.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a new fibre-rich concentrate on the digestibility of horse rations

Abstract: Commercially mixed feeds for light horse feeding are being used more and more and, in recent times, a particular role has been played by mixed feeds characterized by high fibre percentages together with pre-biotic or pro-biotic supplements.Consequently, more data about these new feeds are required. The apparent digestibility of a commercially mixed feed containing about 14% crude fibre (CF) as a feed and 1% lactulose was determined by means of 3 in vivo digestibility trials each performed on 4 saddle horses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
2
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 3 publications
4
5
2
11
Order By: Relevance
“…The lower digestibility of diet 3 and the negative result reported in our study for the NDF digestion coefficient of extruded flaxseed have been confirmed in previous researches, where similar results were found for other concentrates (Miraglia et al, 2006a(Miraglia et al, , 2006b(Miraglia et al, and 2008. This is a general problem of total digestibility trials in horses, and it is probably because of the interaction between hay and concentrates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lower digestibility of diet 3 and the negative result reported in our study for the NDF digestion coefficient of extruded flaxseed have been confirmed in previous researches, where similar results were found for other concentrates (Miraglia et al, 2006a(Miraglia et al, , 2006b(Miraglia et al, and 2008. This is a general problem of total digestibility trials in horses, and it is probably because of the interaction between hay and concentrates.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, we studied the digestion coefficients of various types of hay (Corino et al, 1996;Bergero et al, 2004), haylages (Bergero et al, 2002;) and a large number of concentrates, which mainly provided energy (cereals and their by-products; Miraglia et al, 1999aMiraglia et al, , 2006aMiraglia et al, and 2006bPeiretti et al, 2006). The coefficients obtained using the AIA method were comparable with those obtained from the total collection of feces method, and the former method could therefore be used instead of the total collection method.…”
Section: Discussionmentioning
confidence: 89%
“…As dietas com 25% de fibra, em comparação àquelas com 35% de fibra, apresentaram melhores (P<0,01) de coeficientes de digestibilidade de matéria seca, matéria orgânica e energia bruta e menores coeficientes de digestibilidade de celulose (P<0,05) e extrato etéreo (P<0,01), resultados que confirmam os encontrados por Karlsson et al (2000), Drogoul et al (2001) Esperava-se que a dieta com maior porcentagem de concentrado (35% FDN 50:50) proporcionasse melhora na digestibilidade de matéria seca, proteína bruta, matéria orgânica, energia bruta e extrato etéreo e que a dieta com maior porcentagem de volumoso (35% FDN, 60:40) promovesse melhora na digestibilidade dos componentes da fibra (Karlsson et al, 2000;Drogoul et al, 2001;Miraglia et al, 2006). Entretanto, a origem da fibra, do volumoso ou do concentrado e as duas proporções testadas não promoveram diferenças na digestibilidade desses nutrientes.…”
Section: Resultsunclassified
“…A polpa cítrica vem sendo utilizada na dieta de equinos, contudo com poucas pesquisas (FURTADO et al, 2011;OTT et al, 1979;MANZANO et al, 1999;PERALI et al, 2001;MIRAGLIA et al, 2006;PEIRETTI et al, 2006).…”
Section: 4apolpa Cítricaunclassified
“…Apesar do coeficiente de digestibilidade da EB observado ter sido menor do que relatado em outras pesquisas utilizando polpa cítrica (MANZANO et al, 1999;MIRAGLIA et al, 2006), os valores não diferiram entres os níveis de inclusão de polpa cítrica (Tabela 4), indicando que a inclusão desse ingrediente não alterou negativamente a digestibilidade da energia bruta. O constante valor observado entre os tratamentos, também pode ser explicado pela manutenção dos níveis de digestibilidade da FDN e FDA (OLIVEIRA et al, 2002), que proporcionaram substrato constante entre as dietas para degradação pelos microrganismos para produção de energia.…”
Section: Palatabilidadeunclassified